2002
DOI: 10.1074/jbc.m202637200
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Chromogranin A N-terminal Domain by Plasmin Provides a New Mechanism for Regulating Cell Adhesion

Abstract: It has been proposed that chromogranin A (CgA), a protein secreted by many normal and neoplastic neuroendocrine cells, can play a role as a positive or a negative modulator of cell adhesion. The mechanisms that regulate these extracellular functions of CgA are unknown. We show here that plasmin can regulate the anti/pro-adhesive activity of CgA by proteolytic cleavage of the N-terminal domain. Limited proteolytic processing decreased its anti-adhesive activity and induced pro-adhesive effects in fibronectin or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Presence of the insulin B9-23 peptide in secretory granules of islet beta cells and direct delivery of these peptide fragments to the islet DCs has been previously reported [23]. Plasmin in the secretory granules [24] cleaves VS-1 at lysine sites [25]. Thus, the presence of a natural peptide in the region spanning amino acids 27-46 of the VS-1 molecule that overlaps with the ChgA 29-42 epitope is highly probable.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of the insulin B9-23 peptide in secretory granules of islet beta cells and direct delivery of these peptide fragments to the islet DCs has been previously reported [23]. Plasmin in the secretory granules [24] cleaves VS-1 at lysine sites [25]. Thus, the presence of a natural peptide in the region spanning amino acids 27-46 of the VS-1 molecule that overlaps with the ChgA 29-42 epitope is highly probable.…”
Section: Discussionmentioning
confidence: 99%
“…An emerging area of research has demonstrated a novel role for the serine protease plasmin as a prohormone-processing protease in the neuroendocrine system (Parmer et al, 2000;Hoover-Plow et al, 2001;Jiang et al, 2001;Colombo et al, 2002;Q. Jiang et al, 2002;Pang et al, 2004;N.…”
Section: Introductionmentioning
confidence: 99%
“…b Schematic representation of the N-terminal domain of CgA showing the RGD motif and the amphipathic a-helix. Antibody epitope topography and ezrin-binding-protein-50-homology domain [15][16][17][18] are also indicated. mAb 7D1 and 5A8, but not B4E11 can block the CgA/avb6 interaction (RGE) on skin wound healing in mice.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that CgA can also inhibit the adhesion of fibroblasts to various extracellular-matrix proteins, whereas the CgA 1-78 fragment (VS-1) can promote cell adhesion and spreading [15][16][17][18]. CgA and VS-1 can also enhance endothelial cell-cell adhesion and protect the endothelial barrier integrity from vascular leakage induced by tumor necrosis factor alpha [19,20].…”
Section: Introductionmentioning
confidence: 99%